Preventive healthcare services use among transgender young adults. Issue 4 (2nd October 2018) - McRee, Annie-Laurie; Gower, Amy L.; Reiter, Paul L.
ABSTRACT: Background/Aims : Existing research on the health of transgender young adults focuses largely on gender-related care with little attention to important preventive healthcare services such as well-visits, vaccination and screening. Methods : We analyzed data from a national sample of transgender young adults in the United States who were 18–26 years of age and completed an online survey during Fall 2013 ( n = 34). Most respondents were 22–26 years old (59%) and non-Hispanic White (68%). We calculated descriptive statistics (i.e., frequencies and percentages) to describe transgender young adults use of preventive healthcare services, with particular attention to vaccination against human papillomavirus (HPV) and sexual health services. We also examined the acceptability of home-based self-testing for sexually transmitted infections (STIs), which could be a novel strategy for increasing screening among this population. Results : Only 35% of respondents reported either receiving a routine check-up (past year) or initiating the HPV vaccination series (≥ 1 dose). Among unvaccinated respondents, the most commonly reported reasons for not getting HPV vaccine were: not being sexually active (32%); having only one sexual partner (23%); and being unaware of the vaccine (23%). Fewer than half of respondents had been tested for STIs (47%) but most (71%) were willing to use an STI self-test at home. Discussion : Findings suggest that the healthcare needs of transgender young adults are not being adequately addressed. Efforts to increase providers' capacity to effectively and appropriately serve transgender young adults—such as a wider variety of exam, preventive services, and testing options (e.g., self-collected samples)—are needed.